A low-cost double-layer carbon-coated silicon-oxygen-carbon anode, its preparation method and application
Patent Information
- Application Number
- CN202611253796.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-18
- Publication Date
- 2026-10-27
AI Technical Summary
上述方案虽能改善材料的导电性和循环性能,但普遍存在以下问题:(1)气体碳源成本高昂,乙炔市场价格为26~35元/m3,折合每吨2.3~3万元;(2)气相沉积过程中易产生炭黑副产物,影响碳包覆层的致密性和纯度;(3)部分工艺涉及真空炉高温煅烧或PECVD等复杂技术,设备要求高、能耗大,制约了规模化应用
1、本发明通过有机酸桥连的表面预处理技术,成功突破了油砂沥青在氧化亚硅表面难以形成高质量碳包覆层的技术瓶颈。
Smart Images

Figure CN122992037A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of anode material technology, specifically a low-cost double-layer carbon-coated silicon-oxygen-carbon anode, its preparation method, and its application. Background Technology
[0002] With the rapid development of the 3C electronics and new energy vehicle industries, the market demand for lithium-ion batteries is increasing, especially for high-performance batteries with high energy density, long driving range, and fast charging capabilities. However, the traditional lithium-ion battery anode material—graphite—has a theoretical specific capacity of only 372 mAh / g, which is close to its theoretical limit, significantly restricting further improvements in the overall energy density of lithium-ion batteries. In this context, silicon-based anode materials stand out due to their superior theoretical specific capacity of up to 4200 mAh / g and abundant reserves. However, silicon atoms form Li during lithium intercalation. 4.4 Si alloys exhibit uncontrollable volume expansion of approximately 300%, a drastic change that triggers a series of chain reactions: electrode structure damage; rapid degradation of cycle performance; and disruption of the bond between silicon particles and copper current collectors, exacerbating the shedding of active material. In contrast, silicon-oxygen materials offer more moderate characteristics compared to silicon anodes. In silicon-oxygen materials, Si and O are covalently bonded to form a Si-O-Si network. This structure possesses a certain rigidity, which can constrain the disordered expansion of silicon atoms during lithium intercalation to some extent—ultimately reducing the lithium intercalation volume expansion rate from 300% for pure silicon to 118%–200%, a reduction of 1 / 3 to 1 / 2. The battery capacity remains at 1500 mAh / g–2000 mAh / g, a significant improvement over graphite. Therefore, silicon-oxygen materials are considered the most commercially promising next-generation lithium-ion battery anode material. Developing high-performance lithium-ion batteries based on silicon-oxygen anodes has become a crucial research topic in the current battery field, holding significant importance for promoting the further development of new energy technologies.
[0003] In order to improve the cycling stability of silicon-oxygen anode materials, it is necessary to further suppress their volume expansion. At present, carbon coating is the most critical link to improve the cycling performance of silicon suboxide anode materials. In the existing technology, gaseous carbon sources such as methane and acetylene are generally used for chemical vapor deposition carbon coating treatment. For example, CN202210211929 uses methane as carbon source and performs chemical vapor deposition at 900℃~1100℃ to achieve carbon coating; CN202410818462 uses acetylene as carbon source to coat the surface of silicon-oxygen-carbon composite particles with carbon layer and generate conductive carbon black in situ; CN202411732969 uses PECVD technology to construct a double-layer coating structure on the SiO surface. Although the above schemes can improve the conductivity and cycling performance of the materials, they generally have the following problems: (1) The cost of gaseous carbon sources is high, and the market price of acetylene is 26~35 yuan / m 3 (1) The cost is equivalent to RMB 23,000 to 30,000 per ton; (2) Carbon black byproducts are easily generated during the vapor deposition process, which affects the density and purity of the carbon coating layer; (3) Some processes involve complex technologies such as high-temperature calcination in vacuum furnaces or PECVD, which have high equipment requirements and high energy consumption, thus restricting large-scale application. In addition, CN202510005457 uses anhydrous glucose as a carbon source and performs coating by mechanical ball milling combined with high-temperature pyrolysis. Although the cost is low, the uniformity of solid carbon source mechanical coating and the effect of conductive network construction are significantly different from those of vapor deposition.
[0004] To reduce carbon source costs, the applicant team disclosed a method for surface coating of hard carbon using coking wax oil as a carbon source in Chinese invention patent CN121247768A. Coking wax oil is a byproduct of the coking industry, priced at only 4000-5000 yuan / ton, with an aromatic content of 60%-80%. During pyrolysis, it more easily forms a continuous and dense carbon coating layer, showing significant advantages compared to aliphatic hydrocarbons such as methane. However, the successful implementation of this method relies on the fact that hard carbon and coking wax oil are both carbon-based materials with good chemical compatibility, allowing carbon source molecules to easily adsorb, nucleate, and grow uniformly on the hard carbon surface. In contrast, silicon-oxygen materials (SiO) are inorganic non-metallic materials, and their surface chemistry, atomic arrangement, and surface energy differ fundamentally from those of carbon-based materials. Carbon molecules generated from the pyrolysis of coking wax oil exhibit high adsorption energy barriers, low nucleation density, and weak interfacial bonding on the SiO surface, making it difficult to form a continuous and dense carbon coating layer. Furthermore, SiO is prone to disproportionation reactions at high temperatures (2SiO→Si+SiO2), further altering its surface state and interfering with the stability of the carbon deposition process. Therefore, directly applying the coking wax oil coating method to SiO substrates cannot achieve the same level of carbon coating on hard carbon substrates.
[0005] In recent years, researchers have begun to explore dual-layer coating strategies to further improve the electrochemical performance of silicon-oxygen anode materials. For example, CN202110349581 uses liquid-phase / solid-phase coating to form the first carbon layer and gas-phase coating to form the second carbon layer. The synergistic effect of the two carbon layers improves cycle performance. However, the carbon layers formed by solid-phase or liquid-phase coating have poor uniformity, high impurity content, and are mainly physically attached to the substrate, making them prone to delamination during long-term cycling. CN202311153442 uses titanium-zirconium cooxide as the inner coating layer and pyrolytic carbon as the outer coating layer. Although titanium-zirconium cooxide can improve ionic / electronic conductivity, the coating layer also lacks chemical bonding with the substrate, and the introduction of metal oxides increases the inactive mass, causing a certain loss in the specific capacity of the material. CN202211166319 achieves pre-magnesium coating and double-layer carbon coating simultaneously through a "one-pot method." The inner layer is a loose carbon layer formed by the pyrolysis of a solid carbon source, while the outer layer is a dense carbon layer formed by the pyrolysis of a gaseous carbon source. However, it is difficult to precisely control the uniformity and thickness of the carbon layer during the magnesothermic reaction, affecting the batch stability of the material. In addition, some schemes use ethylene tar as a raw material to prepare coating materials through molecular distillation or polymerization reactions for surface modification of graphite or hard carbon. However, these schemes also suffer from the problem of insufficient chemical bonding between the coating layer and the substrate, and weak interfacial adhesion, making it difficult to meet the requirements for coating layer bonding strength in silicon-oxygen anodes under repeated volume expansion conditions.
[0006] In summary, the following core technical challenges still exist in the existing technology: (1) The high cost of gaseous carbon sources restricts the commercial application of silicon-oxygen-carbon anode materials; (2) Low-cost carbon sources (such as coking wax oil) are difficult to form a high-quality carbon coating layer on the SiO surface due to the "inorganic-organic" interface compatibility problem between the SiO substrate and the carbon source; (3) In the existing double-layer coating scheme, there is a lack of chemical bonding between the coating layer and the SiO substrate, resulting in weak interfacial bonding and insufficient long-term cycle stability. Therefore, how to establish a strong chemical bond between the SiO substrate and the coating layer while maintaining the high uniformity and high purity of the carbon coating layer, so that low-cost carbon sources can form a high-quality carbon coating layer on the SiO surface, has become a technical problem that urgently needs to be solved in this field. Summary of the Invention
[0007] To address the shortcomings of the existing technologies, this invention provides a low-cost method for pretreating the surface of silicon suboxide, a carbon-coated silicon-oxygen-carbon anode, and its application. Its main features are as follows: First, a specific organic acid containing unsaturated double bonds is used to treat the surface of silicon suboxide powder. The carboxyl groups of the organic acid undergo an esterification reaction with the silanol groups (Si-OH) on the surface of the silicon suboxide, grafting the organic acid onto the silicon suboxide surface. Then, the double bonds of the grafted organic acid undergo a Diels-Alder reaction with thiophene-type sulfides in a preferred high-sulfur oil sands pitch. Simultaneously, the residual carboxyl groups of the organic acid form hydrogen bonds with sulfoxide in the oil sands pitch. Through these chemical bonding processes, the oil sands pitch is uniformly coated onto the surface of the silicon suboxide. During high-temperature treatment, the oil sands pitch coating layer is transformed in situ into a highly ordered carbon sheet layer with a loose overall structure through a liquid-phase carbonization process. Finally, the modified SiO powder was surface-coated using chemical vapor deposition (CVD). The previously formed pitch carbon coating layer provides nucleation sites for subsequent CVD carbon coating, significantly improving the uniformity, density, and interfacial bonding strength of the carbon layer. This allows for the construction of a second dense pyrolytic carbon coating layer, resulting in a silicon-oxygen-carbon anode with a double-layer carbon coating. By implementing this invention, the preparation cost is reduced by 40%–73% while improving the electrochemical performance of the prepared silicon-oxygen-carbon anode. This results in a high first-cycle discharge specific capacity of 1700 mAh / g–2300 mAh / g, an initial coulombic efficiency of 84%–92%, and a capacity retention rate of 80%–90% after 800 cycles. This provides a lithium-ion battery anode material solution that combines significant economic efficiency with high performance, achieving the preparation of low-cost, high-performance silicon-oxygen-carbon anode materials.
[0008] Based on the above technical objectives, the present invention adopts the following technical solution: This invention protects a low-cost method for preparing a double-layer carbon-coated silicon-oxygen-carbon anode, comprising the following steps: S1. Silica suboxide is esterified with an organic acid containing unsaturated double bonds in an anhydrous solvent to obtain modified silica suboxide with surface grafted organic acid.
[0009] S2. The modified silica suboxide with surface grafted organic acid is reacted with oil sand asphalt. Through the Diels-Alder reaction of the double bond of organic acid with the thiophene sulfur in the oil sand asphalt, and the hydrogen bonding of the residual carboxyl group of organic acid with the sulfoxide sulfur in the oil sand asphalt, the oil sand asphalt is chemically bonded to the surface of silica suboxide, resulting in modified silica suboxide uniformly coated with oil sand asphalt.
[0010] S3. Using coking wax oil as a carbon source, the main component of coking wax oil is aromatic hydrocarbons with a high aromatic content, which is beneficial for forming a dense and high-strength coating layer during the coating process. The coking wax oil is introduced from the coking wax oil storage tank into the steam generator, and then preheated to the coking wax oil vaporization temperature to generate uniform coking wax oil steam.
[0011] S4. The modified silicate uniformly coated with oil sand asphalt is loaded into the CVD reactor, and protective gas is introduced to remove the air in the CVD reactor.
[0012] S5. Heat the CVD reactor to the pyrolysis temperature of the coking wax oil, and then introduce a mixture of coking wax oil vapor and protective gas to begin carbon deposition.
[0013] S6. During the reaction, the incompletely deposited coking wax vapors, along with the protective gas, enter the circulation system and are reintroduced into the steam generator for reuse, achieving efficient utilization of the carbon source. After the reaction is complete, heating is stopped, and the mixture is cooled to room temperature under a protective atmosphere.
[0014] S7. The product is removed from the CVD reactor and sieved to obtain a low-cost double-layer carbon-coated silicon-oxygen-carbon anode, namely the target material SiO@C anode material.
[0015] Preferably, in step S1, the organic acid containing unsaturated double bonds is selected from at least one of maleic acid, maleic anhydride, acrylic acid, methacrylic acid, itaconic acid, and fumaric acid. These organic acids all contain a carboxyl group capable of esterification with the silanol groups on the surface of silicon suboxide, and simultaneously contain unsaturated double bonds capable of undergoing a Diels-Alder reaction with thiophene sulfide. Maleic acid and maleic anhydride, due to the presence of conjugated double bonds in their molecular structure, exhibit higher reactivity in the Diels-Alder reaction with thiophene; maleic acid or maleic anhydride is particularly preferred.
[0016] Preferably, in step S1, the anhydrous solvent is selected from at least one of toluene, xylene, cyclohexane, and n-heptane.
[0017] Preferably, in step S1, the mass ratio of the organic acid containing unsaturated double bonds to silicon dioxide is 5~20:100, more preferably 10~15:100.
[0018] Preferably, in step S1, the esterification reaction temperature is 60℃~120℃, more preferably 80℃~100℃. The esterification reaction time is 2h~12h, more preferably 4h~8h.
[0019] Preferably, in step S2, the sulfur structure of the oil sands bitumen is characterized by: thiophene sulfur accounting for 40% to 80% of the total sulfur content, and sulfoxide sulfur accounting for 5% to 20% of the total sulfur content. The total sulfur content of the oil sands bitumen is 3wt% to 10wt%, preferably 4wt% to 8wt%.
[0020] Preferably, in step S2, the number-average molecular weight M of the oil sands bitumen is... n The temperature range is 500~5000℃, preferably 800~3800℃. The softening point of the oil sands bitumen is 50~220℃, preferably 100~200℃. The carbon residue of the oil sands bitumen is 25%~55%, preferably 30%~45%. The toluene-insoluble content of the oil sands bitumen is 15%~40%, preferably 20%~35%.
[0021] Preferably, in step S2, the mass ratio of oil sand asphalt to modified silicate grafted with organic acid on the surface is 5~30:100, more preferably 10~20:100.
[0022] Preferably, in step S2, the Diels-Alder reaction temperature is 60℃~100℃, more preferably 80℃~90℃. The reaction time is 4h~12h, more preferably 6h~8h.
[0023] Preferably, in step S3, the initial boiling point of the coking wax oil is 140℃~300℃, the 90% boiling range temperature is 300℃~500℃, the saturated content by mass percentage is 10%~20%, the aromatic content by mass percentage is 70%~90%, and the mass percentages of gums and asphaltenes are both <5%. This coking wax oil is inexpensive, and more importantly, it has a high aromatic content.
[0024] Preferably, in step S3, the steam generator includes direct heating type, indirect heating type, thin film evaporation type, and falling film evaporation type.
[0025] Preferably, in step S1, the particle size of the SiO powder is 6.5 μm to 25 μm. The median particle size D50 of the negative electrode material is generally around 10 μm. Particle size control has a significant impact on its electrochemical performance. If the particle size is too small, it will lead to poor cycle performance; if the particle size is too large, it will affect the quality of the electrode and thus affect the electrochemical performance.
[0026] Preferably, in step S4, the CVD reaction apparatus includes a chemical vapor deposition furnace, a tubular furnace, a fluidized bed, and a rotary kiln.
[0027] Preferably, in step S4, the protective gas includes nitrogen, argon, and helium, and the gas flow rate of the protective gas is 0.2 L / (kg·min) to 15 L / (kg·min).
[0028] Preferably, in step S5, the pyrolysis temperature of the coking wax oil is 400℃~1000℃, the heating rate is 0.5℃ / min~25℃ / min, the steam flow rate of the coking wax oil is 0.1L / (kg·min)~15L / (kg·min), and the pyrolysis time is 0.5h~5h.
[0029] Preferably, in step S6, the circulation system is selected from one or more of the following: condensation separation unit, gas purification unit, and reheating unit.
[0030] This invention also protects the low-cost double-layer carbon-coated silicon-oxygen-carbon anode prepared by the above method. The low-cost double-layer carbon-coated silicon-oxygen-carbon anode is SiO powder coated with a carbon layer. The particle size of the low-cost double-layer carbon-coated silicon-oxygen-carbon anode is 8μm~30μm, and the thickness of the carbon layer is 5nm~40nm. If the coated carbon layer is too thin, it cannot provide sufficient suppression of SiO expansion, resulting in a decrease in cycle performance; if the coated carbon layer is too thick, the deposition time is long, the cost is high, and the increase in carbon content will reduce the capacity / energy density and reduce rate performance.
[0031] This invention also protects the application of the above-mentioned low-cost double-layer carbon-coated silicon-oxygen-carbon anode in lithium-ion batteries. When a coin cell is assembled using the low-cost double-layer carbon-coated silicon-oxygen-carbon anode, the first-cycle discharge specific capacity of the low-cost double-layer carbon-coated silicon-oxygen-carbon anode is 1700mAh / g~2300mAh / g at a current density of 0.1Ah / g, the first coulombic efficiency is 84%~92%, and the capacity retention rate after 800 cycles is 80%~90%.
[0032] Compared with the prior art, the technical solution of the present invention has the following beneficial effects: 1. This invention successfully overcomes the technical bottleneck of forming a high-quality carbon coating layer on the surface of oil sand asphalt by means of organic acid bridging surface pretreatment technology.
[0033] Oil sands bitumen, as a low-cost carbon source, has a molecular structure dominated by polycyclic aromatic hydrocarbons and lacks active functional groups that can directly bond with the surface of silica suboxide. Furthermore, silica suboxide is an inorganic non-metallic material, and there is an "inorganic-organic" interface incompatibility problem between it and oil sands bitumen. When oil sands bitumen is directly used to coat the surface of silica suboxide, the coating layer has poor uniformity and weak interfacial bonding, making it difficult to form a continuous and dense carbon coating layer. To address this technical challenge, this invention pre-treats the surface of silica suboxide before carbon deposition: First, the carboxyl groups of an organic acid undergo an esterification reaction with the silanol groups on the silica suboxide surface, grafting the organic acid onto the silica suboxide surface and introducing carbon-carbon double bonds and free carboxyl groups. Then, the double bonds of the organic acid react with the thiophene sulfur in the oil sands bitumen in a Diels-Alder reaction, while the residual carboxyl groups of the organic acid form hydrogen bonds with the sulfoxide sulfur in the oil sands bitumen. Through chemical bonding, the oil sands bitumen is uniformly coated onto the silica suboxide surface, resulting in modified silica suboxide with active carboxyl groups. This surface pretreatment significantly enhances the interfacial bonding between oil sand pitch and the silica-substrate substrate, enabling the oil sand pitch to spread evenly and bond firmly on the silica-substrate surface. This provides an ideal interfacial environment for subsequent CVD carbon coating of coking wax oil, successfully applying two low-cost carbon sources, oil sand pitch and coking wax oil, to the carbon coating of silica-substrate anode materials.
[0034] 2. This invention significantly improves the electrochemical performance of the material through the synergistic effect of carboxylation pretreatment of silica surface, chemical grafting of oil sands pitch, and CVD carbon coating of coking wax oil. After surface pretreatment, the primary carbon layer formed by the oil sands pitch fixed on the silica surface through chemical bonds not only has a strong bond with the substrate, but the residual active carboxyl groups on the surface also provide abundant nucleation sites for subsequent CVD carbon deposition of coking wax oil, enabling the pyrolysis carbon layer of coking wax oil to grow uniformly and densely. The double-layer carbon coating structure composed of the primary carbon layer of oil sands pitch and the CVD carbon layer of coking wax oil is tightly connected to the silica substrate through chemical bonds, which can effectively suppress the volume expansion of silica during charge and discharge, prevent carbon layer peeling and electrode structure damage, thereby significantly improving the cycle stability of the material. At the same time, the graphitized carbon layer formed by the high aromatic content (70%~90%) of coking wax oil during pyrolysis has good electronic conductivity, which together with the carbon skeleton formed by the carbonization of oil sands pitch to construct a highly efficient electronic conductivity network, which can improve the rate performance of the material. The heteroatoms inherent in oil sands bitumen, such as thiophene sulfur, sulfoxide sulfur, and carbazole nitrogen, embed into the carbon framework after carbonization, forming polar sites. This improves the wettability of the electrolyte on the carbon layer, promotes rapid lithium-ion transport at the interface, and enhances the initial coulombic efficiency. Under these synergistic effects, the low-cost bilayer carbon-coated silicon-oxygen-carbon anode obtained in this invention achieves an initial discharge specific capacity of 1700 mAh / g to 2300 mAh / g, an initial coulombic efficiency of 84% to 92%, and a capacity retention rate stable at 80% to 90% after 800 cycles, demonstrating excellent overall electrochemical performance.
[0035] 3. This invention, through the synergistic design of organic acid bridging pretreatment and a coking wax oil steam recycling system, effectively avoids the adverse effects of carbon black byproducts during CVD and significantly improves carbon source utilization efficiency. Because the adsorption energy barrier and nucleation density of carbon molecules from coking wax oil pyrolysis are high on the untreated silica surface, direct CVD deposition results in a large number of carbon source molecules homogeneously nucleating in the gas phase to form carbon black particles. These carbon black particles, on the one hand, deposit as a loose adhesion layer on the material surface, reducing the density and structural integrity of the carbon coating layer; on the other hand, they increase the specific surface area of the material, exacerbating side reactions between the electrode and the electrolyte, leading to increased irreversible capacity loss. This invention, through organic acid bridging pretreatment, pre-fixes oil sand pitch onto the silica surface with chemical bonds, allowing the carbon molecules from coking wax oil pyrolysis to preferentially grow orderly on the modified silica surface rather than homogeneously nucleating in the gas phase. This effectively suppresses the formation of carbon black byproducts and ensures the density and purity of the carbon coating layer. Meanwhile, by setting up a coking wax oil vapor recycling system, the incompletely deposited coking wax oil vapor is condensed, separated, purified, and reheated before being reintroduced into the CVD reaction device, which achieves efficient utilization of carbon source, reduces waste of coking wax oil and exhaust gas emissions, and further reduces preparation costs.
[0036] 4. This invention offers significant economic advantages. It utilizes two low-cost industrial byproducts, oil sands pitch and coking wax oil, as carbon sources, requiring only a small amount of organic acid as a bridging agent. The surface pretreatment process is simple, the operating conditions are mild, and expensive equipment is not needed. Furthermore, the coking wax oil steam recycling system further improves carbon source utilization and reduces raw material consumption. Compared to traditional CVD carbon coating processes using pure organic carbon source gases (such as acetylene or methane) for extended periods, this invention employs a synergistic carbon coating strategy combining the primary carbon layer from oil sands pitch and the CVD carbon layer from coking wax oil, significantly improving carbon coating efficiency and reducing preparation costs by 40% to 73%. The resulting carbon-coated silicon-oxygen-carbon anode exhibits electrochemical performance comparable to products coated using pure organic carbon sources via CVD, combining significant economic advantages with high performance. This provides a low-cost, high-performance silicon-oxygen-carbon anode material solution for lithium-ion batteries. Attached Figure Description
[0037] Figure 1 This is a process flow diagram for the preparation of the low-cost double-layer carbon-coated silicon-oxygen-carbon anode of the present invention.
[0038] Figure 2This is a schematic diagram of the low-cost double-layer carbon-coated silicon-oxygen-carbon anode of the present invention. The left side is a schematic cross-sectional view of the overall double-layer carbon-coated structure, which consists of a SiO core, an inner pitch carbon layer, and an outer pyrolytic carbon layer from the inside out. The right side is a magnified view of a part of the structure. The upper part is a high-resolution structural diagram of the pitch carbon layer, which has a large interlayer spacing, a loose structure, and N / S heteroatoms distributed between the layers. The lower part is a high-resolution structural diagram of the pyrolytic carbon layer, which has a small interlayer spacing, a dense structure, and exhibits graphitization-like characteristics.
[0039] Figure 3 The images show a comparison of the morphology of CVD carbon coating on the SiO surface under different conditions. The left side shows the sample coated with coking wax oil without surface pretreatment (Comparative Example 1), where the carbon layer on the surface of the SiO particles is loose and a large number of carbon black particles are generated. The right side shows the sample coated with coking wax oil after surface pretreatment with S1+S2 of the present invention (Example 5), where the carbon layer on the surface of the SiO particles is uniform and dense and there are very few carbon black particles. Detailed Implementation
[0040] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0041] This invention provides a low-cost double-layer carbon-coated silicon-oxygen-carbon anode, whose low-cost characteristics and performance advantages are specifically reflected in the following aspects: This invention addresses the problem of poor interfacial compatibility and difficulty in achieving uniform and dense adhesion of the coating layer between oil sands asphalt and silica (SiO) due to the difference in "inorganic-organic" interface properties. It provides a surface pretreatment method: First, an organic acid containing unsaturated double bonds undergoes an esterification reaction with the silanol groups on the SiO surface, grafting the organic acid onto the SiO surface. Then, the double bonds of the grafted organic acid react with thiophene sulfur in the oil sands asphalt via a Diels-Alder reaction. Simultaneously, the residual carboxyl groups of the organic acid form hydrogen bonds with sulfoxide sulfur in the oil sands asphalt. Through this dual chemical bonding, the oil sands asphalt is uniformly and firmly coated onto the SiO surface, forming a modified layer rich in active carboxyl groups. Finally, using coking wax oil as a carbon source, carbon is deposited on the modified SiO surface using chemical vapor deposition to obtain a low-cost, double-layer carbon-coated silicon-oxygen-carbon anode. This invention utilizes the synergistic effect of organic acid bridging pretreatment and oil sand pitch chemical bonding pre-coating to provide abundant nucleation sites for subsequent CVD carbon deposition, significantly improving the uniformity, density, and interfacial bonding strength of the carbon layer. Furthermore, a coking wax oil steam recycling system enables efficient utilization of the carbon source. This invention reduces preparation costs by 40%–73% while achieving a high first-cycle discharge specific capacity of 1700 mAh / g–2300 mAh / g, an initial coulombic efficiency of 84%–92%, and a capacity retention rate of 80%–90% after 800 cycles for the resulting carbon-coated silicon-oxygen-carbon anode. This provides a lithium-ion battery anode material solution that combines significant economic efficiency with high performance.
[0042] Carbon Source Selection: This invention uses oil sands bitumen and coking wax oil as dual carbon sources. Oil sands bitumen is a byproduct of petroleum processing, while coking wax oil is a byproduct of delayed coking units. Both are low-cost industrial byproducts, with market prices far lower than traditional gaseous carbon sources such as methane, ethane, and acetylene. Simultaneously, the thiophene sulfur and sulfoxide sulfur functional groups abundant in oil sands bitumen can be chemically bonded to the surface of silicate to form a primary carbon layer; the high aromatic content (70%~90%) of coking wax oil can form a dense, graphitized carbon layer. The two carbon sources are synergistically complementary in function and cost, making them suitable for large-scale industrial production.
[0043] Cost control: This invention achieves cost control through both carbon source selection and process optimization. Firstly, it utilizes two low-cost industrial byproducts—oil sand pitch and coking wax oil—to replace traditional pure organic gaseous carbon sources, significantly reducing raw material costs. Secondly, by setting up a coking wax oil steam recycling system, undeposited coking wax oil steam is recovered and reused, improving carbon source utilization and reducing raw material waste and exhaust emissions. Under these dual cost controls, the preparation cost of this invention is 40%–73% lower than that of traditional pure gaseous carbon source CVD coating processes, providing economic feasibility for large-scale industrial production.
[0044] Performance Enhancement: The organic acid bridging pretreatment and dual-carbon-source synergistic carbon coating strategy of this invention significantly improve the overall electrochemical performance of the material. The organic acid bridging layer chemically bonds oil sands pitch to the surface of silica suboxide, forming a primary carbon layer firmly bonded to the substrate. The residual carboxyl groups on its surface provide abundant nucleation sites for CVD carbon deposition in coking wax oil, resulting in a uniform and dense double-layer carbon coating structure. This structure is tightly connected to the silica suboxide substrate through chemical bonds, effectively suppressing volume expansion during charge and discharge, preventing carbon layer peeling, and improving cycle stability. After carbonization, heteroatoms such as thiophene sulfur, sulfoxide sulfur, and carbazole nitrogen in the oil sands pitch are embedded in the carbon skeleton to form polar sites, improving electrolyte wettability and lithium-ion interfacial transport rate, and increasing the initial coulombic efficiency. Under the above synergistic effect, the low-cost double-layer carbon-coated silicon-oxygen-carbon anode obtained by this invention achieves an initial discharge specific capacity of 1700~2300 mAh / g, an initial coulombic efficiency of 84%~92%, and a capacity retention rate of 80%~90% after 800 cycles. Compared to existing technologies, the CN202410818462 scheme does not mention the initial coulomb efficiency, the CN202411732969 scheme has the highest initial coulomb efficiency of 87.92% and the 50-cycle capacity retention rate of 88.5%, and the CN202510005457 scheme has the highest initial coulomb efficiency of 70.59% and the 100-cycle capacity retention rate of 57.04%. The present invention has significant advantages in both initial coulomb efficiency and long-cycle stability.
[0045] The technical solution of the present invention will be further studied using the following embodiments. The specific research methods and results are shown below: Example 1 A low-cost method for preparing a double-layer carbon-coated silicon-oxygen-carbon anode, such as... Figure 1 As shown, the specific process of this embodiment is as follows: First, prepare the raw materials. Weigh 20.0 g of silica powder with a particle size D50 of 15 μm and dry it at 120 °C for 2 h to remove surface adsorbed water. Disperse the dried silica powder in 200 mL of anhydrous toluene and sonicate for 15 min. Add 3.0 g of maleic acid (mass ratio of maleic acid to silica powder is 15:100) and stir at 90 °C for 6 h under nitrogen protection. After the reaction is complete, cool to room temperature, centrifuge, wash twice with anhydrous ethanol, and vacuum dry at 80 °C for 4 h to obtain modified silica grafted with maleic acid. Disperse the obtained modified silica in 150 mL of anhydrous toluene and sonicate for 15 min. Add 2.25 g of oil sands pitch and stir at 85 °C for 8 h under nitrogen protection. After the reaction is complete, cool to room temperature, centrifuge, wash once with toluene, and vacuum dry at 80 °C for 4 h to obtain modified silica coated with oil sands pitch. Coking wax oil with an initial boiling point of 203℃ and a 90% boiling range of 350℃ was selected as the carbon source. Modified silica coated with oil sand pitch was evenly spread inside the quartz boat of the CVD reactor. After sealing, the reaction tubes of the CVD reactor were purged with high-purity nitrogen at a flow rate of 1.5 L / min for 30 min to completely remove air. Subsequently, under continuous nitrogen protection, the reaction zone of the CVD reactor was heated to 1000℃ at a nitrogen flow rate of 1.0 L / (Kg·min) and maintained at a constant temperature of 10℃ / min. After the temperature stabilized, the steam generator was started to vaporize the preheated coking wax oil. The coking wax oil vapor was mixed with the nitrogen carrier gas in the protective gas / carrier gas system and then introduced into the reaction zone at a flow rate of 0.5 L / (Kg·min) to begin the carbon deposition process. The total reaction time was 5 h. During this process, the unreacted coking wax oil vapor enters the circulation system through the outlet of the CVD reactor, where it is captured and recovered by the condensation and separation unit. The light components are reintroduced into the steam generator inlet to participate in the recycling, thereby achieving efficient utilization of the carbon source.
[0046] After the reaction was completed, heating was stopped and the carbon source was turned off. The CVD reactor was allowed to cool naturally to room temperature under a nitrogen atmosphere. After cooling, the product was removed and sieved to obtain a carbon-coated silicon-oxygen-carbon anode, which is the final target material, SiO@C anode material. In the obtained SiO@C anode material, a continuous and uniform double-layer carbon coating structure was formed on the surface of SiO particles. The primary carbon layer formed by the carbonization of oil sand pitch and the carbon layer deposited by CVD of coking wax oil together constitute a carbon coating layer with a total thickness of 33 nm. This SiO@C anode material was used as the active material and mixed with the conductive agent Super P and the binder CMC / SBR at a mass ratio of 8:1:1 to form a negative electrode sheet. The electrode was then assembled into a CR2016 coin cell in an argon glove box for electrochemical testing. At a current density of 0.1 A / g, relative to Li +Tests were conducted within a voltage window of 0.01V to 1.5V for the SiO@C anode material. The initial discharge specific capacity reached 1638mAh / g, and the initial coulombic efficiency was 86.59%. After 800 charge-discharge cycles, its capacity retention remained at 84%.
[0047] Example 2 A low-cost method for preparing a double-layer carbon-coated silicon-oxygen-carbon anode, such as... Figure 1 As shown, the specific process of this embodiment is as follows: First, prepare the raw materials. Weigh 20.0 g of silica powder with a particle size D50 of 15 μm and dry it at 120 °C for 2 h to remove surface adsorbed water. Disperse the dried silica powder in 200 mL of anhydrous toluene and sonicate for 15 min. Add 2.0 g of maleic acid (mass ratio of maleic acid to silica powder is 10:100) and stir at 100 °C for 8 h under nitrogen protection. After the reaction, cool to room temperature, centrifuge, wash twice with anhydrous ethanol, and vacuum dry at 80 °C for 4 h to obtain modified silica grafted with maleic acid. Disperse the obtained modified silica in 150 mL of anhydrous toluene and sonicate for 15 min. Add 4.0 g of oil sands pitch and stir at 90 °C for 8 h under nitrogen protection. After the reaction, cool to room temperature, centrifuge, wash once with toluene, and vacuum dry at 80 °C for 4 h to obtain modified silica coated with oil sands pitch. Coking wax oil with an initial boiling point of 203℃ and a 90% boiling range of 350℃ was selected as the carbon source. Modified silica coated with oil sand pitch was evenly spread inside the quartz boat of the CVD reactor. After sealing, the reaction tubes of the CVD reactor were purged with high-purity nitrogen at a flow rate of 1.5 L / min for 30 min to completely remove air. Subsequently, under continuous nitrogen protection, the reaction zone of the CVD reactor was heated to 800℃ at a nitrogen flow rate of 3.0 L / (Kg·min) and a heating rate of 10℃ / min, and maintained at a constant temperature. After the temperature stabilized, the steam generator was started to vaporize the preheated coking wax oil. The coking wax oil vapor was mixed with the nitrogen carrier gas in the protective gas / carrier gas system and then introduced into the reaction zone at a flow rate of 0.5 L / (Kg·min) to begin the carbon deposition process. The total reaction time was 2 hours. During this process, the unreacted coking wax oil vapor enters the circulation system through the outlet of the CVD reactor, where it is captured and recovered by the condensation and separation unit. The light components are reintroduced into the steam generator inlet to participate in the recycling, thereby achieving efficient utilization of the carbon source.
[0048] After the reaction was complete, heating was stopped and the carbon source was turned off. The CVD reactor was allowed to cool naturally to room temperature under a nitrogen atmosphere. After cooling, the product was removed and sieved to obtain a carbon-coated silicon-oxygen-carbon anode, the final target material, SiO@C anode material. In the obtained SiO@C anode material, a continuous and uniform double-layer carbon coating structure was formed on the surface of the SiO particles. The primary carbon layer formed by the carbonization of oil sand pitch and the carbon layer deposited by CVD with coking wax oil together constitute a carbon coating layer with a total thickness of 16 nm. Using this SiO@C anode material as the active material, it was mixed with the conductive agent Super P and the binder CMC / SBR at a mass ratio of 8:1:1 to form a negative electrode sheet. This sheet was then assembled into a CR2016 coin cell in an argon glove box for electrochemical testing. The results were obtained at a current density of 0.1 A / g, relative to Li... + Tested within a voltage window of 0.01V~1.5V for / Li, the SiO@C anode material achieved an initial discharge specific capacity of 2265mAh / g and an initial coulombic efficiency of 84.89%. After 800 charge-discharge cycles, its capacity retention remained at 89%.
[0049] Example 3 A low-cost method for preparing a double-layer carbon-coated silicon-oxygen-carbon anode, such as... Figure 1 As shown, the specific process of this embodiment is as follows: First, prepare the raw materials. Weigh 20.0 g of silica powder with a particle size D50 of 15 μm and dry it at 120 °C for 2 h to remove surface adsorbed water. Disperse the dried silica powder in 200 mL of anhydrous toluene and sonicate for 15 min. Add 2.4 g of maleic acid (mass ratio of maleic acid to silica powder is 12:100) and stir at 90 °C for 4 h under nitrogen protection. After the reaction is complete, cool to room temperature, centrifuge, wash twice with anhydrous ethanol, and vacuum dry at 80 °C for 4 h to obtain modified silica grafted with maleic acid. Disperse the obtained modified silica in 150 mL of anhydrous toluene and sonicate for 15 min. Add 2.0 g of oil sands pitch and stir at 80 °C for 6 h under nitrogen protection. After the reaction is complete, cool to room temperature, centrifuge, wash once with toluene, and vacuum dry at 80 °C for 4 h to obtain modified silica coated with oil sands pitch. Coking wax oil with an initial boiling point of 203℃ and a 90% boiling range of 350℃ was selected as the carbon source. Modified silica coated with oil sand pitch was evenly spread inside the quartz boat of the CVD reactor. After sealing, the reaction tubes of the CVD reactor were purged with high-purity nitrogen at a flow rate of 1.5 L / min for 30 min to completely remove air. Subsequently, under continuous nitrogen protection, the reaction zone of the CVD reactor was heated to 800℃ at a nitrogen flow rate of 0.5 L / (Kg·min) and maintained at a constant temperature of 10℃ / min. After the temperature stabilized, the steam generator was started to vaporize the preheated coking wax oil. The coking wax oil vapor was mixed with the nitrogen carrier gas in the protective gas / carrier gas system and then introduced into the reaction zone at a flow rate of 0.5 L / (Kg·min) to begin the carbon deposition process. The total reaction time was 5 hours. During this process, the unreacted coking wax oil vapor enters the circulation system through the outlet of the CVD reactor, where it is captured and recovered by the condensation and separation unit. The light components are reintroduced into the steam generator inlet to participate in the recycling, thereby achieving efficient utilization of the carbon source.
[0050] After the reaction was completed, heating was stopped and the carbon source was turned off. The CVD reactor was allowed to cool naturally to room temperature under a nitrogen atmosphere. After cooling, the product was removed and sieved to obtain a carbon-coated silicon-oxygen-carbon anode, which is the final target material, SiO@C anode material. In the obtained SiO@C anode material, a continuous and uniform double-layer carbon coating structure was formed on the surface of SiO particles. The primary carbon layer formed by the carbonization of oil sand pitch and the carbon layer deposited by CVD of coking wax oil together constitute a carbon coating layer with a total thickness of 10 nm. This SiO@C anode material was used as the active material and mixed with the conductive agent Super P and the binder CMC / SBR at a mass ratio of 8:1:1 to form a negative electrode sheet. The electrode was then assembled into a CR2016 coin cell in an argon glove box for electrochemical testing. At a current density of 0.1 A / g, relative to Li +Tests were conducted within a voltage window of 0.01V to 1.5V for the SiO@C anode material. The initial discharge specific capacity reached 2204 mAh / g, with an initial coulombic efficiency of 92%. After 800 charge-discharge cycles, its capacity retention remained at 86.44%.
[0051] Example 4 A low-cost method for preparing a double-layer carbon-coated silicon-oxygen-carbon anode, such as... Figure 1 As shown, the specific process of this embodiment is as follows: First, prepare the raw materials. Weigh 20.0 g of silica powder with a particle size D50 of 15 μm and dry it at 120 °C for 2 h to remove surface adsorbed water. Disperse the dried silica powder in 200 mL of anhydrous toluene and sonicate for 15 min. Add 2.6 g of maleic acid (mass ratio of maleic acid to silica powder is 13:100) and stir at 90 °C for 8 h under nitrogen protection. After the reaction, cool to room temperature, centrifuge, wash twice with anhydrous ethanol, and vacuum dry at 80 °C for 4 h to obtain modified silica grafted with maleic acid. Disperse the obtained modified silica in 150 mL of anhydrous toluene and sonicate for 15 min. Add 2.25 g of oil sands pitch and stir at 90 °C for 6 h under nitrogen protection. After the reaction, cool to room temperature, centrifuge, wash once with toluene, and vacuum dry at 80 °C for 4 h to obtain modified silica coated with oil sands pitch. Coking wax oil with an initial boiling point of 203℃ and a 90% boiling range of 350℃ was selected as the carbon source. Modified silica coated with oil sand pitch was evenly spread inside the quartz boat of the CVD reactor. After sealing, the reaction tubes of the CVD reactor were purged with high-purity nitrogen at a flow rate of 1.5 L / min for 30 min to completely remove air. Subsequently, under continuous nitrogen protection, the reaction zone of the CVD reactor was heated to 1000℃ at a nitrogen flow rate of 1 L / (Kg·min) and maintained at a constant temperature of 10℃ / min. After the temperature stabilized, the steam generator was started to vaporize the preheated coking wax oil. The coking wax oil vapor was mixed with the nitrogen carrier gas in the protective gas / carrier gas system and then introduced into the reaction zone at a flow rate of 0.5 L / (Kg·min) to begin the carbon deposition process. The total reaction time was 1.5 h. During this process, the unreacted coking wax oil vapor enters the circulation system through the outlet of the CVD reactor, where it is captured and recovered by the condensation and separation unit. The light components are reintroduced into the steam generator inlet to participate in the recycling, thereby achieving efficient utilization of the carbon source.
[0052] After the reaction was completed, heating was stopped and the carbon source was turned off. The CVD reactor was allowed to cool naturally to room temperature under a nitrogen atmosphere. After cooling, the product was removed and sieved to obtain a carbon-coated silicon-oxygen-carbon anode, which is the final target material, SiO@C anode material. In the obtained SiO@C anode material, a continuous and uniform double-layer carbon coating structure was formed on the surface of the SiO particles. The primary carbon layer formed by the carbonization of oil sand pitch and the carbon layer deposited by CVD of coking wax oil together constitute a carbon coating layer with a total thickness of 8 nm. This SiO@C anode material was used as the active material and mixed with the conductive agent Super P and the binder CMC / SBR at a mass ratio of 8:1:1 to form a negative electrode sheet. The electrode was then assembled into a CR2016 coin cell in an argon glove box for electrochemical testing. At a current density of 0.1 A / g, relative to Li + Tests were conducted within a voltage window of 0.01V to 1.5V for the SiO@C anode material. The initial discharge specific capacity reached 1848mAh / g, and the initial coulombic efficiency was 84.79%. After 800 charge-discharge cycles, its capacity retention remained at 81.37%.
[0053] Example 5 A low-cost method for preparing a double-layer carbon-coated silicon-oxygen-carbon anode, such as... Figure 1 As shown, the specific process of this embodiment is as follows: First, prepare the raw materials. Weigh 20.0 g of silica powder with a particle size D50 of 9 μm and dry it at 120 °C for 2 h to remove surface adsorbed water. Disperse the dried silica powder in 200 mL of anhydrous toluene and sonicate for 15 min. Add 2.8 g of maleic acid (mass ratio of maleic acid to silica powder is 14:100) and stir at 90 °C for 8 h under nitrogen protection. After the reaction, cool to room temperature, centrifuge, wash twice with anhydrous ethanol, and vacuum dry at 80 °C for 4 h to obtain modified silica grafted with maleic acid. Disperse the obtained modified silica in 150 mL of anhydrous toluene and sonicate for 15 min. Add 2.25 g of oil sands pitch and stir at 85 °C for 8 h under nitrogen protection. After the reaction, cool to room temperature, centrifuge, wash once with toluene, and vacuum dry at 80 °C for 4 h to obtain modified silica coated with oil sands pitch. Coking wax oil with an initial boiling point of 203℃ and a 90% boiling range of 350℃ was selected as the carbon source. Modified silica coated with oil sand pitch was evenly spread inside the quartz boat of the CVD reactor. After sealing, the reaction tubes of the CVD reactor were purged with high-purity nitrogen at a flow rate of 1.5 L / min for 30 min to completely remove air. Subsequently, under continuous nitrogen protection, the reaction zone of the CVD reactor was heated to 1000℃ at a nitrogen flow rate of 1 L / (Kg·min) and maintained at a constant temperature of 10℃ / min. After the temperature stabilized, the steam generator was started to vaporize the preheated coking wax oil. The coking wax oil vapor was mixed with the nitrogen carrier gas in the protective gas / carrier gas system and then introduced into the reaction zone at a flow rate of 0.5 L / (Kg·min) to begin the carbon deposition process. The total reaction time was 2.5 h. During this process, the unreacted coking wax oil vapor enters the circulation system through the outlet of the CVD reactor, where it is captured and recovered by the condensation and separation unit. The light components are reintroduced into the steam generator inlet to participate in the recycling, thereby achieving efficient utilization of the carbon source.
[0054] After the reaction was completed, heating was stopped and the carbon source was turned off. The CVD reactor was allowed to cool naturally to room temperature under a nitrogen atmosphere. After cooling, the product was removed and sieved to obtain a carbon-coated silicon-oxygen-carbon anode, which is the final target material, SiO@C anode material. In the obtained SiO@C anode material, a continuous and uniform double-layer carbon coating structure was formed on the surface of the SiO particles. The primary carbon layer formed by the carbonization of oil sand pitch and the carbon layer deposited by CVD of coking wax oil together constitute a carbon coating layer with a total thickness of 20 nm. This SiO@C anode material was used as the active material and mixed with the conductive agent Super P and the binder CMC / SBR at a mass ratio of 8:1:1 to form a negative electrode sheet. The electrode was then assembled into a CR2016 coin cell in an argon glove box for electrochemical testing. Tested at a current density of 0.1 A / g and a voltage window of 0.01 V to 1.5 V relative to Li+ / Li, the SiO@C anode material achieved an initial discharge specific capacity of 2250 mAh / g and an initial coulombic efficiency of 92.30%. After 800 charge-discharge cycles, its capacity retention remained at 90.00%.
[0055] Comparative Example 1 A method for preparing a carbon-coated silicon-oxygen-carbon anode, the difference between this comparative example and the above embodiments is that the surface pretreatment steps S1 and S2 are omitted, and the CVD coating process is performed directly. The specific process of this comparative example is as follows:
[0056] First, raw material preparation was carried out. 20.0 g of silica powder with a particle size D50 of 9 μm was weighed, and coking wax oil with an initial boiling point of 203℃ and a 90% boiling range of 350℃ was selected as the carbon source. The SiO powder was evenly spread in the quartz boat of the CVD reactor. After sealing, the reaction tube of the CVD reactor was purged with high-purity nitrogen at a flow rate of 1.5 L / min for 30 min to completely remove air. Subsequently, under continuous nitrogen protection, the reaction zone of the CVD reactor was heated to 1000℃ at a nitrogen flow rate of 1 L / (Kg·min) and maintained at a constant temperature of 10℃ / min. After the temperature stabilized, the steam generator was started to vaporize the preheated coking wax oil. The coking wax oil vapor was mixed with the nitrogen carrier gas in the protective gas / carrier gas system and then introduced into the reaction zone at a flow rate of 0.5 L / (Kg·min) to begin the carbon deposition process. The total reaction time was 5 h. During this process, the unreacted coking wax oil vapor enters the circulation system through the outlet of the CVD reactor, where it is captured and recovered by the condensation and separation unit. The light components are reintroduced into the steam generator inlet to participate in the recycling, thereby achieving efficient utilization of the carbon source.
[0057] After the reaction was complete, heating was stopped and the carbon source was turned off. The CVD reactor was allowed to cool naturally to room temperature under a nitrogen atmosphere. After cooling, the product was removed and sieved to obtain a carbon-coated silicon-oxygen-carbon anode, which is the final target material, SiO@C anode material. In the obtained product, although a carbon coating layer was formed on the surface of the SiO particles, the coating layer had poor uniformity, with local areas showing carbon layer accumulation or exposure, and carbon black particles could be observed in the product.
[0058] The SiO@C anode material was used as the active material, and a negative electrode sheet was prepared by mixing it with the conductive agent Super P and the binder CMC / SBR in a mass ratio of 8:1:1. The electrode was then assembled into a CR2016 coin cell in an argon glove box for electrochemical testing. Tests were conducted at a current density of 0.1 A / g and a voltage window of 0.01 V to 1.5 V relative to Li⁺ / Li. The material showed an initial discharge specific capacity of 1520 mAh / g and an initial coulombic efficiency of 62.37%. After 300 charge-discharge cycles, its capacity was 164.56 mAh / g; after 800 cycles, the capacity almost completely disappeared.
[0059] Table 1. Comparison of specific process parameters and results between Examples 1-5 and Comparative Example 1 All examples used the same batch of coking wax oil, and the battery test conditions were all 0.1 A / g current density.
[0060] Example 6 A low-cost method for preparing a double-layer carbon-coated silicon-oxygen-carbon anode, such as... Figure 1 As shown, the specific process of this embodiment is as follows: First, prepare the raw materials. Weigh 20.0 g of silica powder with a particle size D50 of 6.5 μm and dry it at 120 °C for 2 h to remove surface adsorbed water. Disperse the dried silica powder in 200 mL of anhydrous toluene and sonicate for 15 min. Add 2.2 g of maleic acid (mass ratio of maleic acid to silica powder is 11:100) and stir at 80 °C for 4 h under nitrogen protection. After the reaction, cool to room temperature, centrifuge, wash twice with anhydrous ethanol, and vacuum dry at 80 °C for 4 h to obtain modified silica grafted with maleic acid. Disperse the obtained modified silica in 150 mL of anhydrous toluene and sonicate for 15 min. Add 2 g of oil sands pitch and stir at 80 °C for 6 h under nitrogen protection. After the reaction, cool to room temperature, centrifuge, wash once with toluene, and vacuum dry at 80 °C for 4 h to obtain modified silica coated with oil sands pitch. Coking wax oil with an initial boiling point of 203℃ and a 90% boiling range of 350℃ was selected as the carbon source. Modified silica coated with oil sand pitch was evenly spread inside the quartz boat of the CVD reactor. After sealing, the reaction tubes of the CVD reactor were purged with high-purity nitrogen at a flow rate of 1.5 L / min for 30 min to completely remove air. Subsequently, under continuous nitrogen protection, the reaction zone of the CVD reactor was heated to 400℃ at a nitrogen flow rate of 0.2 L / (Kg·min) and maintained at a constant temperature of 10℃ / min. After the temperature stabilized, the steam generator was started to vaporize the preheated coking wax oil. The coking wax oil vapor was mixed with the nitrogen carrier gas in the protective gas / carrier gas system and then introduced into the reaction zone at a flow rate of 0.2 L / (Kg·min) to begin the carbon deposition process. The total reaction time was 5 h. During this process, the unreacted coking wax oil vapor enters the circulation system through the outlet of the CVD reactor, where it is captured and recovered by the condensation and separation unit. The light components are reintroduced into the steam generator inlet to participate in the recycling, thereby achieving efficient utilization of the carbon source.
[0061] After the reaction was complete, heating was stopped and the carbon source was turned off. The CVD reactor was allowed to cool naturally to room temperature under a nitrogen atmosphere. After cooling, the product was removed and sieved to obtain a carbon-coated silicon-oxygen-carbon anode, which is the final target material, SiO@C anode material.
[0062] Example 7 A low-cost method for preparing a double-layer carbon-coated silicon-oxygen-carbon anode, such as... Figure 1 As shown, the specific process of this embodiment is as follows: First, prepare the raw materials. Weigh 20.0 g of silica powder with a particle size D50 of 20 μm and dry it at 120 °C for 2 h to remove surface adsorbed water. Disperse the dried silica powder in 200 mL of anhydrous toluene and sonicate for 15 min. Add 3 g of maleic acid (mass ratio of maleic acid to silica powder is 14:100) and stir at 100 °C for 8 h under nitrogen protection. After the reaction, cool to room temperature, centrifuge, wash twice with anhydrous ethanol, and vacuum dry at 80 °C for 4 h to obtain modified silica grafted with maleic acid. Disperse the obtained modified silica in 150 mL of anhydrous toluene and sonicate for 15 min. Add 4.0 g of oil sand pitch and stir at 90 °C for 8 h under nitrogen protection. After the reaction, cool to room temperature, centrifuge, wash once with toluene, and vacuum dry at 80 °C for 4 h to obtain modified silica coated with oil sand pitch. Coking wax oil with an initial boiling point of 203℃ and a 90% boiling range of 350℃ was selected as the carbon source. Modified silica coated with oil sand pitch was evenly spread inside the quartz boat of the CVD reactor. After sealing, the reaction tubes of the CVD reactor were purged with high-purity nitrogen at a flow rate of 1.5 L / min for 30 min to completely remove air. Subsequently, under continuous nitrogen protection, the reaction zone of the CVD reactor was heated to 600℃ at a nitrogen flow rate of 15 L / (Kg·min) and a heating rate of 10℃ / min, and maintained at a constant temperature. After the temperature stabilized, the steam generator was started to vaporize the preheated coking wax oil. The coking wax oil vapor was mixed with the nitrogen carrier gas in the protective gas / carrier gas system and then introduced into the reaction zone at a flow rate of 15 L / (Kg·min) to begin the carbon deposition process. The total reaction time was 0.5 h. During this process, the unreacted coking wax oil vapor enters the circulation system through the outlet of the CVD reactor, where it is captured and recovered by the condensation and separation unit. The light components are reintroduced into the steam generator inlet to participate in the recycling, thereby achieving efficient utilization of the carbon source.
[0063] After the reaction was complete, heating was stopped and the carbon source was turned off. The CVD reactor was allowed to cool naturally to room temperature under a nitrogen atmosphere. After cooling, the product was removed and sieved to obtain a carbon-coated silicon-oxygen-carbon anode, which is the final target material, SiO@C anode material.
[0064] The above description of the disclosed embodiments enables those skilled in the art to make or use the invention. Various modifications to these embodiments will be readily apparent to those skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the invention. Therefore, the invention is not to be limited to the embodiments shown herein, but is to be accorded the widest scope consistent with the principles and novel features disclosed herein.
Claims
1. A method for preparing a low-cost double-layer carbon-coated silicon-oxygen-carbon anode, characterized in that, Includes the following steps: Silica suboxide is esterified with an organic acid containing unsaturated double bonds in an anhydrous solvent to obtain modified silica suboxide with surface grafted organic acid. Modified silica suboxide with surface-grafted organic acid was reacted with oil sand asphalt. Through the Diels-Alder reaction of the double bond of organic acid with the thiophene sulfur in the oil sand asphalt, and the hydrogen bonding of the residual carboxyl group of organic acid with the sulfoxide sulfur in the oil sand asphalt, the oil sand asphalt was chemically bonded to the surface of silica suboxide, resulting in modified silica suboxide uniformly coated with oil sand asphalt. Modified silica suboxide uniformly coated with oil sand asphalt is loaded into a CVD reactor. After removing the air from the CVD reactor, the CVD reactor is heated to the pyrolysis temperature of coking wax oil. A mixture of coking wax oil vapor and protective gas is introduced to deposit carbon on the surface of the modified silica suboxide uniformly coated with oil sand asphalt, thus obtaining a low-cost double-layer carbon-coated silicon-oxygen-carbon anode.
2. The method for preparing a low-cost double-layer carbon-coated silicon-oxygen-carbon anode according to claim 1, characterized in that, Organic acids containing unsaturated double bonds are selected from at least one of maleic acid, maleic anhydride, acrylic acid, methacrylic acid, itaconic acid, and fumaric acid.
3. The method for preparing a low-cost double-layer carbon-coated silicon-oxygen-carbon anode according to claim 1, characterized in that, The mass ratio of organic acids containing unsaturated double bonds to silicon dioxide is 5~20:
100.
4. The method for preparing a low-cost double-layer carbon-coated silicon-oxygen-carbon anode according to claim 1, characterized in that, The esterification reaction temperature is 60℃~120℃, and the time is 2h~12h.
5. The method for preparing a low-cost double-layer carbon-coated silicon-oxygen-carbon anode according to claim 1, characterized in that, Number-average molecular weight M of oil sands bitumen n The mass ratio of oil sand asphalt to modified silicate grafted with organic acid is 5-30:100, ranging from 500 to 5000.
6. The method for preparing a low-cost double-layer carbon-coated silicon-oxygen-carbon anode according to claim 1, characterized in that, The Diels-Alder reaction temperature is 60℃~100℃, and the reaction time is 4h~12h.
7. The method for preparing a low-cost double-layer carbon-coated silicon-oxygen-carbon anode according to claim 1, characterized in that, The carbon deposition method is as follows: SiO powder is placed in a CVD reactor, the temperature of the CVD reactor is set to the pyrolysis temperature of coking wax oil (400℃~1000℃), coking wax oil vapor is introduced, the flow rate of coking wax oil vapor is 0.1L / (kg·min)~15L / (kg·min), and pyrolysis is carried out for 0.5h~5h.
8. A low-cost double-layer carbon-coated silicon-oxygen-carbon anode, characterized in that, It is prepared by the preparation method described in any one of claims 1 to 7.
9. The low-cost double-layer carbon-coated silicon-oxygen-carbon anode according to claim 8, characterized in that, The low-cost double-layer carbon-coated silicon-oxygen-carbon anode is a SiO powder coated with a carbon layer. The particle size of the low-cost double-layer carbon-coated silicon-oxygen-carbon anode is 8μm~30μm, and the thickness of the carbon layer is 5nm~40nm.
10. The application of the low-cost double-layer carbon-coated silicon-oxygen-carbon anode as described in claim 8 in lithium-ion batteries.
Citation Information
Patent Citations
Double-layer carbon-coated silicon monoxide negative electrode material as well as preparation method and application thereof
CN113363479A
Doped induced disproportionation carbon-coated silicon monoxide material as well as preparation method and application thereof
CN114613982A
Preparation method of magnesium-containing silicon monoxide negative electrode material for lithium ion battery
CN115663125A
Carbon-titanium-zirconium co-oxide-silicon monoxide material as well as preparation method and application thereof
CN117038925A
Composite negative electrode material and preparation method thereof
CN118833817A